2020
DOI: 10.3346/jkms.2020.35.e190
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Renal Dialysis on All-Cause Mortality in Older Patients with Hip Fracture: a Korean Nationwide Cohort Study

Abstract: Background: The purpose of this study was to analyze the all-cause mortality rate over time after elderly hip fracture in end-stage renal disease (ESRD) patients with dialysis, using a Korean nationwide claims database. Methods: This retrospective nationwide study identified subjects from the Korean National Health Insurance Service-Senior cohort (NHIS-Senior). The NHIS-Senior (total of 588,147 participants) was constructed by 10% random sampling and was designed to represent the elderly living in Korea. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…In concurrence with studies that have reported predictors of mortality risk following hip surgery, 17,34,36,37 our study also demonstrated that male sex, high preoperative serum creatinine, low baseline handgrip strength, and high CCI were poor indictors of a high risk of mortality within 1 year of hip surgery in the geriatric population. In addition, long surgical delay after a falling accident was an important predictor for mortality risk in this study.…”
Section: Discussionsupporting
confidence: 90%
“…In concurrence with studies that have reported predictors of mortality risk following hip surgery, 17,34,36,37 our study also demonstrated that male sex, high preoperative serum creatinine, low baseline handgrip strength, and high CCI were poor indictors of a high risk of mortality within 1 year of hip surgery in the geriatric population. In addition, long surgical delay after a falling accident was an important predictor for mortality risk in this study.…”
Section: Discussionsupporting
confidence: 90%
“…All of the included studies were retrospective cohort studies. 26,[28][29][30][31][32][33][39][40][41][42] The data is summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported age as the range. 26,39 Here, the age of the patients with chronic kidney disease not undergoing hemodialysis was 76.9 ± 2.5 years, whereas for the patients with chronic kidney disease undergoing hemodialysis the average age was 73.6 ± 3.3 years. The average age of healthy participants was 75.3 ± 2.6 years.…”
Section: Participant Informationmentioning
confidence: 93%
“…Nevertheless, our results are consistent with the hip fracture literature, which found that patients with ESRD are at higher risk for readmission and complications after surgery. 9 , 17 , 19 , 22 , 23 , 41 When examining specific causes for 90-day readmission, SSI was the most common in both cohorts. Interestingly, there was no concurrent increased risk of reoperation, suggesting these were likely superficial SSI amenable to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…ESRD is associated with increased mortality, medical complications, readmission, and revision surgery in hip fractures. 17 , 23 , 32 , 41 More generally, renal disease has been associated with increased rates of postoperative infection, osteonecrosis, nonunion, and implant failure. 9 , 19 , 22 …”
mentioning
confidence: 99%